COMPARATIVE ANALYSIS OF SOCIO- ECONOMIC AND CULTIVATION VARIABLES AND ATTITUDES OF SUGARCANE GROWERS ABOUT SUGARCANE PRODUCTION AND MARKETING IN DHARMAPURI DISTRICT, TAMILNADU - Sakunthala, K.; Thanigasalam, G. (International Journal of Psychosocial Rehabilitation, 2020)
Agriculture is one of the most significant sector of the Indian Economy. Agriculture is the only means of living for almost two thirds of the workers in India. The agriculture sector of India has occupied 43% of India’s geographical area, and it contributing 16.1% of India’s GDP. There are number of crops grown by farmers in India, it includes different food crops, commercial crops, oil seeds etc. Sugarcane is one of the important commercial crops grown in India. The sugarcane cultivation and sugar industry in India plays a vital role towards socio-economic development in the rural areas by mobilizing rural resources and generating higher income and employment opportunities. The objective of the study is to analyze the relationship between the socio-economic and cultivation variables and attitudes of sugarcane growers about production and marketing of sugarcane in Dharmapuri district, Tamilnadu. The multi-stage random sampling technique was adopted. The total of 30 village panchayats and 150 sugarcane growers were determined as the sample of the study. The study found that the socio economic variable education have highly negative influence on the attitude of sugarcane growers about production and marketing of sugarcane and the cultivation variable number of acre cultivation have positive influence on the attitude of sugarcane growers about production and marketing of sugarcane except financial aspects. On the other side the socio economic variable gender does not have any influence on the attitude of sugarcane growers about production and marketing of sugarcane. The variable annual income has positive influence on the attitude of sugarcane growers about the production and financial aspects of sugarcane growing. The variable age have the positive influence on production aspects and negative influence on financial aspects of sugarcane growing. The variable occupation has the negative influence on production, marketing and financial aspects of sugarcane growing. The variable experience in sugarcane growing has the negative influence on the attitude of production and harvesting aspects of sugarcane growing. Thus the study conclude that majority of the sugarcane growers were not satisfied about the performance of sugar mills particularly financial and harvesting aspects.